Rural Granaries in Northern Gaul (Sixth Century BCE - Fourth Century CE) From Archaeology to Economic History - Martin, Stéphane (Radboud Studies in Humanities, 2019)
Rural granaries in northern Gaul (sixth century BCE - fourth century CE) offers a comprehensive account of rural grain storage and its role in the economy of a key region of the Roman Empire. Readership: All interested in the economic history and in the agriculture of the Roman Empire, and more generally of pre-industrial agrarian economies.